Antibacterial and antioxidant activities of Piper cubeba L. berries extract and its cytotoxicity effect on 3T3 human fibroblast and HEPG2 cell lines - Lou, Shuai Qiang (2021)
Human-pathogenic bacterial has been increase dramatic in the past decades, then the antibacterial resistance was recognized widely as a grave threat to the global health in the 21st century. The most important oxygen-containing free radicals in many disease states are hydroxyl radical, superoxide anion radical, hydrogen peroxide, oxygen singlet, hypochlorite, nitric oxide radical, and peroxynitrite radical. This study aimed to determine the antibacterial and antioxidant activities of Piper cubeba L. extract and its toxicity on 3T3 and HepG2 cell lines. Methanol and ethanol were the extraction solvents used for dried P. cubeba L. berries using maceration methods. and the selected crude extract was fractionated using liquid-liquid partition with the solvents of hexane, chloroform and ethyl acetate. The antibacterial activities of P. cubeba L. berries crude extract and its fraction were determined in term of disc diffusion assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against four bacterial: Bacillus megaterium, Bacillus subtilis, Bacillus pumilus and Klebsiella pneumoniae. The total phenolic contents (TPC) were analysed using Folin-Ciocalteau method of P. cubeba L. berries extract and its fractions and antioxidant activity of were determined using 2,2-diphenyl-1-picrylhydryzyl (DPPH) radical scavenging assay. The cytotoxicity of P. cubeba L. was evaluated using 3-[4,5-dimethylthiazole-2-yl]-2,5- diphenyltetrazolium bromide (MTT) assay on 3T3 human fibroblast and HepG2 cell lines. The active compounds were identified by using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatograph-Mass Spectrometry (LC-MS). Diameter of inhibition zones of methanol extracts against the selected bacterial were ranged from 8.00 ± 0.10 to 11.00 ± 0.00 nm. MICs of methanol and ethanol crude extracts were ranged from 0.16 mg/mL to 1.25 mg/mL and 0.62 mg/mL to 1.25 mg/mL, respectively. The methanol and ethanol both crude extracts can kill the bacterial with the values of MBC 2.50 mg/mL. The total phenolic of methanol crude extract was 0.59 ± 0.01 mg/GAE/g and ethanol crude extract was 0.66 ± 0.02 mg GAE/g. The DPPH results of methanol and ethanol crude extracts displayed IC50 were 546.14 ± 3.28 μg/mL and 472.43 ± 5.21 μg/mL, respectively. The cytotoxic effect on 3T3 fibroblast cell line of methanol and ethanol both crude extracts showed non-cytotoxic, however, the cytotoxic effect on HepG2 cell line of methanol crude extract with value of IC50 13.14 ± 3.77 μg/mL, while the ethanol crude extract had the IC50 value of 28.40 ± 1.44 μg/mL. The inhibition zoon of fractions was ranged from 7.20 ± 0.16 mm to 10.00 ± 0.16 mm. The MICs of fractions were ranged from 0.078 mg/mL to 0.625 mg/mL and the value of MBC of fractions was ranged from 0.156 mg/mL to 1.250 mg/mL. The total phenolic content in the fractions of hexane, chloroform and ethyl acetate was 0.45 ± 0.02 mg GAE/g, 0.69 ± 0.12 mg GAE/g and 0.86 mg GAE/g, respectively. And the DPPH values of fractions of hexane, chloroform and ethyl acetate displayed IC50 was 3.614 ± 0.24 mg/mL, 0.197 ± 0.02 mg/mL and 0.098 ± 0.03 mg/mL, respectively. Hexane, chloroform and ethyl acetate fractions illustrated cytotoxic effect on HepG2 cell line with the IC50 values of 11.05 ± 0.86 μg/mL, 21.00 ± 0.43 μg/mL, 29.77 ± 0.99 μg/mL, respectively while ethyl acetate displayed non-cytotoxic effect on 3T3 fibroblast cell line. Further purification to isolate the potentially active compound would be taken in the future. The major volatile components were identified using GC-MS, including beta-cubebene, muurolene, alfa-copaene and alfa-cubebene with the antibacterial activity, cubebol, spathulenol and viridflorol with the antioxidant activity and elemene, eugenol and caryophyllene with the anticancer activity. Hemiarensin with antibacterial activity, myricetin with antioxidant and ellagic acid with anticancer activity, were identified using LC-MS.